Design with a Positive Lens: An affirmative approach to designing information and organizations - Avital, M.; Lyytinen, K.; Boland, R.; Butler, B.; Dougherty, D.; Fineout, M.; Jansen, W.; Levina, N.; Rifkin, W.; Venable, John (Reagan Ramsower, 2006)
Design forms one critical paradigmatic view that pervades organizational studies, management, and information systems research. Building on the discussions in the First Working Conference on Designing Information and Organizations with a Positive Lens, we chart the potential contribution of positive design to the shaping of organizations, work processes, artifacts, communication networks, and information technologies. The figure of speech "Design with a Positive Lens," or in short, "Positive Design," connotes here a distinctive perspective on design that is less focused on the detection of errors associated with gaining control and more concerned with human-centered design associated with the shaping of hopeful organizations and a thriving future. The paper examines how positive design can contribute to the design of information systems and organizations as related to five broad-scale areas: design of high performance work processes; positive design methods and techniques: cooperation and collaboration across boundaries to promote positive change; positive organizational design, and design science and practice. In this paper we aspire to promote the emerging cross-disciplinary discourse between scholars and designers that will foster positive organizational and technological design.